Pengaruh Tingkat Pengetahuan Santri Mengenai Perbankan Syariah Terhadap Minat Menggunakan Produk Bank Syariah - Muflihah, Hani; Sanusi, Sanusi; Nuraeni, Anisa; Inayatullah, Deden (STAI La Tansa Mashiro, 2023)
Economy in people's daily lives are two things that cannot be separated. In Islam, economics is something that is given special attention. Islam has an economic view based on the rules of the Islamic religion that we know today, namely Islamic economics or Sharia economics. The role of sharia banks in general is to carry out continuous outreach to students about sharia banking knowledge as a whole. The formulation of the problem in this research is (1) Does students' knowledge of sharia banking influence the interest of Darul Fawaz Subis students in using sharia banking products, (2) How does the level of knowledge of Darul Fawaz Subis students regarding sharia banking influence? This research method uses quantitative methods. Quantitative methods are methods that focus on numerical data with certain instruments and measuring tools, with data collection techniques using questionnaires. Data analysis in this study used simple linear regression analysis, correlation t test and coefficient of determination. In the T test, the t table results obtained from 48 samples were 1.667. The student knowledge variable regarding sharia banking shows a calculated t result of 9.772 and a t table of 1.667, therefore it can be concluded that 9.772 > 1.667, in the sense that the hypothesis accepted in this research is that Ha and Ho are rejected. It is concluded that students' knowledge of Islamic banking influences their interest in using Islamic banking products. And the influence of variable This means that 66.5 percent of students' interest in sharia banking products is influenced by students' interest in knowledge, the remainder (33.5%) is influenced by other variables outside the research.Keyword: Santri, sharia banking, interests, products.